1987
DOI: 10.1002/1097-0142(19870501)59:9<1611::aid-cncr2820590915>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin in colorectal carcinoma an immunohistochemical study

Abstract: To assess the biological significance of human chorionic gonadotropin (HCG) detection in large bowel carcinomas, we have studied immunohistochemically 50 colorectal carcinomas, 20 adenomas, 8 ulcerative colitis, and 10 normal colonic mucosae. The HCG-immunoreactive cells were found in 26 carcinomas (52%). Positivity was not detected in any normal mucosa or benign lesions. Cells containing HCG predominated in mucinous (80%) and poorly differentiated carcinomas (92%). No trophoblastic differentiation could be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
3

Year Published

1989
1989
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 29 publications
2
19
0
3
Order By: Relevance
“…Ito & Tahara (1983) reported that the rate of metastasis was high and prognosis was poor in cases of hCG-producing gastric cancer. It has been claimed that hCG-positive large bowel cancers show severe local invasion and high rates of lymph node metastasis (Campo et al, 1987). In our study, the presence of hCG-positive tumour cells was associated with aggressive local invasion and the presence of metatases.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Ito & Tahara (1983) reported that the rate of metastasis was high and prognosis was poor in cases of hCG-producing gastric cancer. It has been claimed that hCG-positive large bowel cancers show severe local invasion and high rates of lymph node metastasis (Campo et al, 1987). In our study, the presence of hCG-positive tumour cells was associated with aggressive local invasion and the presence of metatases.…”
Section: Discussionsupporting
confidence: 54%
“…The presence of hCG in cancer tissues has been demonstrated in some patients with colorectal cancer by the immunohistochemical method. According to this report, the presence of hCG-positive cells was associated with greater local invasion and the presence of lymph node and liver metastases (Campo et al, 1987). We have, therefore, studied the incidence of hCG in colorectal cancers and correlated its presence with a variety of clinicopathological parameters.…”
mentioning
confidence: 98%
“…Within the Dukes' stages, hCG-positive tumors carried a worse prognosis but the differences in survival were not statistically significant. In other reports, expression of hCG␤ has been associated directly with reduced survival 21,25 and indirectly through a correlation with poor histological differentiation, 19 tumor invasiveness 18,19,25 and a higher incidence of metastases. 22 However, no correlation between hCG␤ staining and survival was found in 2 studies.…”
Section: Serological and Histological Expression Of Hcg␤ And Survivalmentioning
confidence: 82%
“…We did not observe a correlation between hCG␤ and histological differentiation, which was reported in a previous study. 19 In our study, immunohistochemical expression of hCG␤ was compared with previously reported serum levels of the same patients. hCG␤ in tumor tissue, like in serum, emerged as a prognostic factor in both uni-and multivariate analyses.…”
Section: Serological and Histological Expression Of Hcg␤ And Survivalmentioning
confidence: 96%
See 1 more Smart Citation